Study on Bearing Capacity of the Existing Engineering Pile Group without Lateral Displacement during Dynamic Top-Down Construction - Zhen Wang; Yang Zhao; Xuelin Yang; Zhi Ding; Wenwei Zhu; Qingzhong Wang (Advances in Civil Engineering)
The bearing capacity of the vertical underpinning structure system is the key index in the design of top-down construction for adding a basement layer under existing buildings. The influence of the lateral restraint is the most significant under the dynamic construction excavation. For the problem of the bearing capacity of the existing engineering pile group under the top-down construction, the linear eigenvalue stability method was used first to study the influence of the lateral restraints such as the horizontal resistance of soil, the diameter of piles body, and the bending rigidity of the temporary steel bracing on its bearing capacity. The corresponding critical stability load and the effective length coefficient were then obtained. Then, based on the nonlinear extreme point stability method with the initial geometrical imperfection, the amplification range for the effective length coefficient was studied. Finally, based on the current Chinese Code Formula (JGJ 94-2008) and considering the influence of the compression buckling effect of the high cap pile, the present solution of the bearing capacity for the pile body was obtained and compared with the code solution. It turns out that the nonlinear bearing capacity of existing engineering piles group with initial imperfection is smaller than the critical stability load of the linear eigenvalue and increases with the increase of the imperfection amplitude, and the amplification range of the effective length coefficient is 1.10∼1.20. The present solution of the bearing capacity with the compression buckling effect is 1.10∼1.30 times of the code solution, which shows that the code solution is partial to safety, and the residual bearing can be properly considered in the design.